Knowledge and opinion of residents of Caxias do Sul on encephalic death and organ and tissue donation for transplant - Silva, Rafaela Souza da; Souza, Janaína Samantha Martins de (Brazilian Journal of Transplantation, 2021)
Purpose: To identify the knowledge and opinion of a sample of the population of the city of Caxias do Sul about encephalic death and organ and tissue donation for transplantation. Methods: This is an exploratory study with a quantitative approach performed with 122 residents of the city of Caxias do Sul – Rio Grande do Sul, randomly selected among the population over 18 years old. Data collection was performed in the waiting room of a medium-sized hospital care and in a private college institution from August to September of 2018. Data were analyzed through the IBM SPSS Software, by linear regression and the Pearson correlation, considering as significance level p <0.05. Results: the majority of participants (96.7%) is in favor of organ donation, and (82.8%) would authorize the donation of their organs after death, having as main motivator helping others and save lives. The main reasons against the donation are attachment to family and religion. Many believe in the existence of organ trading in Brazil, and that there is a possibility of error in the encephalic death diagnosis established by the doctor. Most have already received information on organ donation mainly through the media and health professionals. Conclusion: the majority of participants has a positive attitude toward organ donation, and they present partial knowledge about the donation process. It is required more educational campaigns and incentives to donate, as the greater the understanding of the family, the greater the security at the moment of decision to the organ donation.